2017
DOI: 10.1007/s00204-017-2007-9
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide study of the incidence rate of herb-induced liver injury in Korea

Abstract: Discrepant incidence has been reported regarding the incidence of herb-induced liver injury (HILI). To address the growing worldwide concern of HILI, we evaluated the risk of HILI in a nationwide prospective study. Between April 2013 and January 2016, 1001 inpatients (360 males and 641 females) from 10 tertiary hospitals throughout South Korea were treated with herbal drugs and had their liver enzymes periodically measured. A total of six patients met the criteria for HILI with RUCAM scores ranging from 4 to 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 23 publications
0
51
1
3
Order By: Relevance
“…1,2) In recent years, increasing clinical reports have indicated potential hepatotoxicity of FP in patients, [3][4][5] for instance, Cheung et al showed three cases of acute hepatitis after exposed to FP and its related medicine such as Bu-gu-zhi intramuscular injection, 3) and concerns grow over the health effects of FP. However, the hepatotoxic components and the mechanism of FP-induced hepatotoxicity are not fully understood.…”
mentioning
confidence: 99%
“…1,2) In recent years, increasing clinical reports have indicated potential hepatotoxicity of FP in patients, [3][4][5] for instance, Cheung et al showed three cases of acute hepatitis after exposed to FP and its related medicine such as Bu-gu-zhi intramuscular injection, 3) and concerns grow over the health effects of FP. However, the hepatotoxic components and the mechanism of FP-induced hepatotoxicity are not fully understood.…”
mentioning
confidence: 99%
“…The present result was slightly higher than that of HILI (0.56%, 95% CI [0.07, 1.05]) with 892 patients in a retrospective study(Kim et al, ) and that of HILI (0.43%) with 1169 patients in another retrospective study (Woo et al, ). However, this result was slightly lower than that of HILI (0.60%, 95% CI [0.12, 1.08]) with 1,001 patients in a nationwide prospective study (Cho et al, ) and that of HILI (0.6%) with 4,769 patients in another retrospective study (Lee, Shin, et al, ). These four studies defined the liver injury using the original method (Hayashi, ).…”
Section: Discussionmentioning
confidence: 77%
“…In particular, there is a lack of prospective studies focusing on cases with causality gradings by Roussel Uclaf Causality Assessment Method (RUCAM) . However, some incidence data for such cases have been published . For instance, a recent report from Germany presented, for the first time, liver‐injury data derived from a prospective, large‐scale hospital‐based study of 21 470 patients, who had no liver disease prior to treatment with herbal traditional Chinese medicines (TCM), in which product falsification and adulteration were excluded.…”
Section: Epidemiology Data In Comparisonmentioning
confidence: 99%
“…It is unclear whether the high quality standard applied to the herbal TCM products used in the German hospital may have contributed to the low case numbers . A low incidence of 0.6% for HILI cases was also reported in a prospective study of 1001 patients with RUCAM‐based causality gradings of possible and higher from Korea . In the US State of Delaware, a small, preliminary, and prospective study involving gastroenterologists only, 6 cases per 100 000 adults were reported, corresponding to 1.2 cases of HDS‐induced liver injury per 100 000 adults .…”
Section: Epidemiology Data In Comparisonmentioning
confidence: 99%
See 1 more Smart Citation